1978
DOI: 10.3382/ps.0571599
|View full text |Cite
|
Sign up to set email alerts
|

Low Erucic Acid, Low Glucosinolate Rapeseed Meal, with and without Added Gums in the Layer Diet

Abstract: White Leghorn pullets of two strains were fed 20% of Tower rapeseed meal in the laying diet for one year. The rapeseed meal was manufactured with and without addition of 2% of either Tower or Midas gums. Control birds were fed a soybean meal diet. Each diet was fed to 1018 birds of two commercial lines. Rate of production during a one-year period was similar on all diets. Gums were without effect on any aspect of production. Overall mortality in the experiment was 11.7%, or 6.5% when neoplasms were excluded. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1981
1981
1981
1981

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
3
1
Order By: Relevance
“…The lack of effect on egg size of RSM is contrary to earlier observations that egg weight is reduced when RSM is fed to layers (Summers et al, 1969;March et al, 1972March et al, , 1978. It is likely that the nutritional characteristics of rapeseed Brassica napus cv.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The lack of effect on egg size of RSM is contrary to earlier observations that egg weight is reduced when RSM is fed to layers (Summers et al, 1969;March et al, 1972March et al, , 1978. It is likely that the nutritional characteristics of rapeseed Brassica napus cv.…”
Section: Discussioncontrasting
confidence: 83%
“…More recently, March and MacMillan (1979) reported that excreta from chicks fed rapeseed meal as the source of supplementary protein contained a lower proportion of lipid in the form of soap fatty acids than when soybean meal was the dietary protein supplement. It may also be observed that laying birds fed diets containing rapeseed meal tend to lay smaller eggs than are laid by birds fed diets containing soybean meal (Summers et al, 1969;March et «/., 1972March et «/., , 1978.…”
Section: Introductionmentioning
confidence: 93%
“…Leeson et al (1911) concluded that no deleterious effects accrued from feeding laying birds diets containing RSM to which had been added 1.57o gums. In another study March et al (1978) liBased on the data of Hubbell (1980 Leeson et al (1977), who reported that the addition of SBG or RSG to the diet of laying hens had no effect on body weight but resulted in significantly smaller eggs.…”
mentioning
confidence: 99%
“…It was concluded that while the incidence of LH varied with dietary level of intact glucosinolates, the effects was related more to total intact glucosinolates than to specific glucosinolates, such as progoitrin. MARCH et al, (1978) observed haemorrhage lesions not only in liver but also in other tissue of the birds fed rapeseed meal and suggested the presence of an agent affecting the integrity of the vascular system. et al, (1980) observed that the inclusion of 10% rapeseed meal in broiler diets did not cause severe liver haemorrhage, however, it did produce a significant enlargement of liver; and changes of plasma enzyme activities indicative of damage to the bilary system of the chicks.…”
Section: Effects Of Glucosinolates On Liver In Poultrymentioning
confidence: 90%